Amino Acid Modifications During the Production (Shearing, Sterilization) of Plant-Based Meat Analogues: An Explorative Study Using Pet Food Production as an Example - Wehrmaker, Ariane M.; Zenker, Hannah; De Groot, Wouter; Sanders, Mark; Van Der Goot, Atze Jan; Janssen, Anja E. M.; Keppler, Julia; Bosch, Guido (ACS Food Science & Technology, 2022)
Shear cell technology is a promising method for the production of meat analogues. Meat analogues are also studied as alternative proteins for dogs and cats, which require high-quality protein. This study monitored the effect of shearing, using shear cell technology, and sterilization (26 min at 125.5 degrees C) on selected amino acids, advanced glycation end products (AGEs), lysinoalanine, o-phthalaldehyde-reactive lysine, as well as oxidation markers, free thiols, and dityrosine, in soy protein- and pea protein-based meat analogues. These are compared with animal-based pet foods. Processing resulted in modified amino acids, especially cysteine. Reductions in amino acid levels were higher in the soy-based meat analogue, but markers indicated more pronounced oxidation in the pea-based meat analogue. AGEs and lysinoalanine were not formed on shearing, only during sterilization. Despite extensive thermal treatment, the effects of processing on the protein quality of plant-based products were comparable or less than those in animal-based pet food.
CRIS-Team WoS Importer:2022-11-25

Binding of cml-modified as well as heat-glycated β-lactoglobulin to receptors for ages is determined by charge and hydrophobicity - Zenker, Hannah E.; Teodorowicz, Malgorzata; Ewaz, Arifa; Joost van Neerven, R. J.; Savelkoul, Huub F.J.; De Jong, Nicolette W.; Wichers, Harry J.; Hettinga, Kasper A. (International Journal of Molecular Sciences, 2020)
Intake of dietary advanced glycation end products (AGEs) is associated with inflammation-related health problems. Nε-carboxymethyl lysine (CML) is one of the best characterised AGEs in processed food. AGEs have been described as ligands for receptors present on antigen presenting cells. However, changes in protein secondary and tertiary structure also induce binding to AGE receptors. We aimed to discriminate the role of different protein modifications in binding to AGE receptors. Therefore, β-lactoglobulin was chemically modified with glyoxylic acid to produce CML and compared to β-lactoglobulin glycated with lactose. Secondary structure was monitored with circular dichroism, while hydrophobicity and formation of β-sheet structures was measured with ANS-assay and ThT-assay, respectively. Aggregation was monitored using native-PAGE. Binding to sRAGE, CD36, and galectin-3 was measured using inhibition ELISA. Even though no changes in secondary structure were observed in all tested samples, binding to AGE receptors increased with CML concentration of CML-modified β-lactoglobulin. The negative charge of CML was a crucial determinant for the binding of protein bound CML, while binding of glycated BLG was determined by increasing hydrophobicity. This shows that sRAGE, galectin-3, and CD36 bind to protein bound CML and points out the role of negatively charged AGEs in binding to AGE receptors.
Created from Fastlane, Scopus look-up
Keywords: CD36; Charge; Galectin-3; Glycation; Milk protein; Nε-carboxymethyl lysine; SRAGE

Detection of intact bovine milk proteins after simulated gastrointestinal infant digestion using UHPLC − HRMS - Gensberger-Reigl, Sabrina; Zenker, Hannah (Food Chemistry, 2025)
This study demonstrates the development and application of an ultra-high-performance liquid chromatography coupled with high-resolution mass spectrometry (UHPLC−HRMS) method for the rapid and sensitive identification of intact bovine milk proteins following simulated gastrointestinal infant digestion. The new method enables the differentiation between partially hydrolysed/modified and fully intact proteins. In the raw milk, intact α-lactalbumin was visible on SDS − PAGE until the end of the gastrointestinal digestion, while it was not detected with UHPLC−HRMS. Analysis of both raw and heated milk samples revealed that the method is applicable to various milk types. Interestingly, heated milk showed additional signals in the mass spectrum, indicating non-enzymatic post-translational modifications. The relative abundance of these proteoforms could be followed along digestion. These findings highlight the versatility and sensitivity of UHPLC−HRMS in elucidating protein structures and modifications, providing valuable insights into how simulated digestion affects milk protein composition.
CRIS-Team Scopus Importer:2024-11-29
Keywords: Bovine milk; Casein; Digestion; High-resolution mass spectrometry; Intact protein; Non-enzymatic post-translational modification; α-Lactalbumin; β-Lactoglobulin

Differential effects of dry vs. Wet heating of β-lactoglobulin on formation of sRAGE binding ligands and sIgE epitope recognition - Zenker, Hannah E.; Ewaz, Arifa; Deng, Ying; Savelkoul, Huub F.J.; Van Neerven, R. J.Joost; De Jong, Nicolettew; Wichers, Harry J.; Hettinga, Kasper A.; Teodorowicz, Malgorzata (Nutrients, 2019)
The effect of glycation and aggregation of thermally processed β-lactoglobulin (BLG) on binding to sRAGE and specific immunoglobulin E (sIgE) from cow milk allergic (CMA) patients were investigated. BLG was heated under dry conditions (water activity < 0.7) and wet conditions (in phosphate buffer at pH 7.4) at low temperature (<73ºC) and high temperatures (>90 ºC) in the presence or absence of the milk sugar lactose. Nε-(carboxymethyl)-l-lysine (CML) western blot and glycation staining were used to directly identify glycation structures on the protein fractions on SDS-PAGE. Western blot was used to specify sRAGE and sIgE binding fractions. sRAGE binding was highest under wet-heated BLG independent of the presence of the milk sugar lactose. Under wet heating, high-molecular-weight aggregates were most potent and did not require the presence of CML to generate sRAGE binding ligands. In the dry system, sRAGE binding was observed only in the presence of lactose. sIgE binding affinity showed large individual differences and revealed four binding profiles. Dependent on the individual, sIgE binding decreased or increased by wet heating independent of the presence of lactose. Dry heating required the presence of lactose to show increased binding to aggregates in most individuals. This study highlights an important role of heating condition-dependent protein aggregation and glycation in changing the immunogenicity and antigenicity of cow’s milk BLG.
Created from Fastlane, Scopus look-up
Keywords: Aggregation; Allergenicity; CML; Glycation; IgE binding; SRAGE; β-lactoglobulin

Enhanced Uptake of Processed Bovine β-Lactoglobulin by Antigen Presenting Cells: Identification of Receptors and Implications for Allergenicity - Teodorowicz, Malgorzata; Zenker, Hannah E.; Ewaz, Arifa; Tsallis, Theodoros; Mauser, Andreas; Gensberger-Reigl, Sabrina; de Jong, Nicolette W.; Hettinga, Kasper A.; Wichers, Harry J.; van Neerven, R. J.Joost; Savelkoul, Huub F.J. (Molecular Nutrition & Food Research, 2021)
Scope: β-lactoglobulin (BLG) is a major cow milk allergen encountered by the immune system of infants fed with milk-based formulas. To determine the effect of processing on immunogenicity of BLG, this article characterized how heated and glycated BLG are recognized and internalized by APCs. Also, the effect of heat-induced structural changes as well as gastrointestinal digestion on immunogenicity of BLG is evaluated. Methods and results: The binding and uptake of BLG from raw cow milk and heated either alone (BLG-H) or with lactose/glucose (BLG-Lac and BLG-Glu) to the receptors present on APCs are analyzed by ELISA and cell-binding assays. Heated and glycated BLG is internalized via galectin-3 (Gal-3)and scavenger receptors (CD36 and SR-AI) while binding to the receptor for advanced glycation end products (R AGE) does not cause internalization. Receptor affinity of BLG is dependent on increased hydrophobicity, β-sheet exposure and aggregation. Digested glycated BLG maintained binding to sRAGE and Gal-3 but not to CD36 and SR-AI, and is detected on the surface of APCs. This suggests a mechanism via which digested glycated BLG may trigger innate (via RAGE) and adaptive immunity (via Gal-3). Conclusions: This study defines structural characteristics of heated and glycated BLG determining its interaction with APCs via specific receptors thus revealing enhanced immunogenicity of glycated versus heated BLG.
CRIS-Team Scopus Importer:2021-03-19
Keywords: aggregation of β-lactoglobulin; cow milk processing; digestion of β-lactoglobulin; galactin-3 Maillard reaction ligands; glycation of β-lactoglobulin; RAGE Maillard reaction ligands

Lysine blockage of milk proteins in infant formula impairs overall protein digestibility and peptide release - Zenker, Hannah E.; Van Lieshout, Glenn A.A.; Van Gool, Martine P.; Bragt, Marjolijn C.E.; Hettinga, Kasper A. (Food and Function, 2020)
During heat processing of milk and dairy products, for example infant formula, the Maillard reaction occurs. In vitro and animal studies suggest that Maillard reaction induced lysine blockage impairs protein digestibility. Most studies that investigate the effect of glycation on protein digestion use a mixture of isolated milk protein with reducing sugars. In this study, infant formulas with 6.5%, 8.4%, 11.2%, 14.8%, 20.8%, and 44.5% of blocked lysine (BL) were digested in an in vitro infant digestion model and tested for protein hydrolysis and peptide release. OPA (o-phthalaldehyde) assay was used to assess the degree of protein hydrolysis. SDS-PAGE was conducted to monitor the hydrolysis of specific proteins. Peptides formed after gastric and intestinal digestion were identified by LC/MS. Protein hydrolysis of the 6.5% BL sample was significantly higher after 10 minutes of intestinal digestion compared to all other samples. Most differences were observed after intestinal digestion. A significant change in peptide patterns was observed for the 45% BL sample resulting in a relatively higher number of peptides with more than 14 amino acids. Mainly casein-derived peptides were affected. Overall, the average peptide length was significantly increased for the 44.5% BL glycated product (on average 10.2 amino acids for 6-21% BL vs. 11.4 amino acids for 45% BL; p < 0.001). In conclusion, glycation of milk proteins in an infant formula product can impair overall protein digestibility. These findings emphasize the importance of mild processing and having low BL levels in infant formula to ensure optimal digestion of proteins.
Created from Fastlane, Scopus look-up

No glycation required: Interference of casein in age receptor binding tests - Zenker, Hannah E.; Teodorowicz, Malgorzata; Wichers, Harry J.; Hettinga, Kasper A. (Foods, 2021)
For the determination of the binding of heated cow’s milk whey proteins such as β-lactoglobulin to the receptors expressed on immune cells, inhibition ELISA with the soluble form of the receptor for advanced glycation end products (sRAGE) and scavenger receptor class B (CD36) has been successfully used in the past. However, binding to heated and glycated caseins in this read-out system has not been tested. In this study, inhibition ELISA was applied to measure the binding of cow’s milk casein alone, as well as all milk proteins together, which underwent differential heat treatment, to sRAGE and CD36, and we compared those results to a dot blot read out. Moreover, binding to sRAGE and CD36 of differentially heated milk protein was measured before and after in vitro digestion. Casein showed binding to sRAGE and CD36, independent from the heat treatment, in ELISA, while the dot blot showed only binding to high-temperature-heated milk protein, indicating that the binding is not related to processing but to the physicochemical characteristics of the casein. This binding decreased after passage of casein through the intestinal phase.
Created from Fastlane, Scopus look-up
Keywords: Casein; CD36; Immunogenicity; Milk protein; SRAGE

Peptide release after simulated infant in vitro digestion of dry heated cow’s milk protein and transport of potentially immunoreactive peptides across the caco-2 cell monolayer - Zenker, Hannah E.; Wichers, Harry J.; Tomassen, Monic M.M.; Boeren, Sjef; De Jong, Nicolette W.; Hettinga, Kasper A. (Nutrients, 2020)
Dry heating of cow’s milk protein, as applied in the production of “baked milk”, facilitates the resolution of cow’s milk allergy symptoms upon digestion. The heating and glycation-induced changes of the protein structure can affect both digestibility and immunoreactivity. The immunological consequences may be due to changes in the peptide profile of the digested dry heated milk protein. Therefore, cow’s milk protein powder was heated at low temperature (60 °C) and high temperature (130 °C) and applied to simulated infant in vitro digestion. Digestion-derived peptides after 10 min and 60 min in the intestinal phase were measured using LC-MS/MS. Moreover, digests after 10 min intestinal digestion were applied to a Caco-2 cell monolayer. T-cell epitopes were analysed using prediction software, while specific immunoglobin E (sIgE) binding epitopes were identified based on the existing literature. The largest number of sIgE binding epitopes was found in unheated samples, while T-cell epitopes were equally represented in all samples. Transport of glycated peptide indicated a preference for glucosyl lysine and lactosyl-lysine-modified peptides, while transport of peptides containing epitope structures was limited. This showed that the release of immunoreactive peptides can be affected by the applied heating conditions; however, availability of peptides containing epitopes might be limited.
Created from Fastlane, Scopus look-up
Keywords: Allergenicity; Caco-2 cell; Cow’s milk protein; Glycation; Immunogenicity; Peptides

Receptor Mediated Effects of Advanced Glycation End Products (AGEs) on Innate and Adaptative Immunity: Relevance for Food Allergy - Noriega, Daniela Briceno; Zenker, Hannah; Croes, Cresci-Anne; Ewaz, Arifa; Ruinemans-Koerts, Janneke; Savelkoul, Huub F. J.; Van Neerven, R. J. Joost; Teodorowicz, Malgorzata (Nutrients, 2022)
As of late, evidence has been emerging that the Maillard reaction (MR, also referred to as glycation) affects the structure and function of food proteins. MR induces the conformational and chemical modification of food proteins, not only on the level of IgG/IgE recognition, but also by increasing the interaction and recognition of these modified proteins by antigen-presenting cells (APCs). This affects their biological properties, including digestibility, bioavailability, immunogenicity, and ultimately their allergenicity. APCs possess various receptors that recognize glycation structures, which include receptor for advanced glycation end products (RAGE), scavenger receptors (SRs), galectin-3 and CD36. Through these receptors, glycation structures may influence the recognition, uptake and antigen-processing of food allergens by dendritic cells (DCs) and monocytes. This may lead to enhanced cytokine production and maturation of DCs, and may also induce adaptive immune responses to the antigens/allergens as a result of antigen uptake, processing and presentation to T cells. Here, we aim to review the current literature on the immunogenicity of AGEs originating from food (exogenous or dietary AGEs) in relation to AGEs that are formed within the body (endogenous AGEs), their interactions with receptors present on immune cells, and their effects on the activation of the innate as well as the adaptive immune system. Finally, we review the clinical relevance of AGEs in food allergies.
CRIS-Team WoS Importer:2022-07-22

Regioselective analysis of heat-induced conformational changes of β-lactoglobulin by quantitative liquid chromatography–mass spectrometry analysis of chemical labeling kinetics - Liu, Jiajia; Gensberger-Reigl, Sabrina; Zenker, Hannah; Schichtl, Theresa Maria; Utz, Wolfgang; Pischetsrieder, Monika (Food Chemistry, 2024)
β-Lactoglobulin is a main allergen in cow's milk; its allergenicity is strongly impacted by processing. To understand heat-induced epitope-specific effects, the present study analyzed regiospecific conformational changes of heated native β-lactoglobulin variant A (BLG-A). Complementary fluorescence spectroscopy methods indicated two denaturation phases comprising minor sequential conformational changes (25–75 °C) and complete transitions (80–90 °C). Regioselective conformational changes of BLG-A in the native state (25 °C), sequential (70 °C) and complete transition (90 °C) were determined by quantitative liquid chromatography–mass spectrometry analysis of chemical labeling kinetics covering 14 lysine residues and the N-terminus. Conformational changes in two phases were observed for N-terminus, K8 (both N-terminal chain), K60 (β-sheet C), K75 (β-sheet D), K77 (DE loop), K83 (β-sheet E), K100 and K101 (FG loop). The residues K14 (β-sheet A1), K47 (β-sheet B), K69, K70 (both β-sheet D), and K91 (β-sheet F) were not involved in conformational changes.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Allergenic epitopes; Chemical labeling kinetics; Conformational changes; Heat-processing; Quantitative liquid chromatography–mass spectrometry analysis; β-Lactoglobulin

The effect of low vs. high temperature dry heating on solubility and digestibility of cow's milk protein - Zenker, Hannah E.; Raupbach, Jana; Boeren, Sjef; Wichers, Harry J.; Hettinga, Kasper A. (Food Hydrocolloids, 2020)
Dry heating of cow's milk protein in the presence of the milk sugar lactose leads to a loss of solubility and digestibility. Most studies that investigated the loss of solubility in milk protein powders suggested that, besides structural changes, hydrophobic interaction, hydrogen bonds, disulphide bonds, and Maillard reaction-induced crosslinking are responsible for this. However, little is known about the direct contribution of these inter- and intramolecular interactions on loss of solubility and protein digestibility. Low temperature (60 °C) and high temperature (130 °C) dry heating of cow's milk protein in the presence of lactose was applied after which both the soluble and insoluble fractions were analysed with SDS-PAGE and LC-MS/MS. The Maillard reaction was monitored by quantification of Nε-carboxymethyllysine, Nε-carboxyethyllysine, and pentosidine with LC-MS/MS. Loss of solubility was analysed with solvent solubility tests. Protein hydrolysis after simulated infant in vitro digestion, and after hydrolysis with single enzymes, was monitored using SDS-PAGE and the o-phthaldialdehyde assay. The results indicated that caseins are the main proteins that become insoluble upon dry heating, independent of the heating temperature. The decreased solubility of low temperature dry heated cow's milk protein is induced by hydrogen bonds and hydrophobic interactions and did not impair protein hydrolysis. At the same time, covalent protein crosslinking is an important determinant in protein solubility and digestibility of high temperature dry heated cow's milk protein.
Created from Fastlane, Scopus look-up
Keywords: Crosslinking; Digestibility; Dry heating; Maillard reaction; Milk protein; Solubility